Tissue specific splicing of pre-mRNA porcine mitochondrial transcription factor A - Renčelj, Andrej; Škrlep, Martin; Čandek-Potokar, Meta; Dovč, Peter (Czech Journal of Animal Science, 2018)
Mitochondrial transcription factor A plays, due to its role in replication and transcription of the mitochondrial DNA, an important role in mitochondrial biogenesis and regulation of its activity. In different mammalian species, mitochondrial transcription factor A is present in two different splicing forms. The aim of the study was to verify the presence of both splicing forms and to estimate their ratio in different tissues. The expression levels of both splicing forms in two skeletal muscles (m. semispinalis capitis and m. semimembranosus), heart muscle, brain, spleen, and liver in commercial hybrids and in the autochthonous Krsko polje pig breed are reported. In all analyzed tissues the expression of the long form of the mitochondrial transcription factor A was about one order of magnitude higher compared to the short form, lacking almost the entire exon 4 region. Taking into account the expression ratio of both splicing forms and biological function of the mitochondrial transcription factor A, the possible explanation for the persistence of both forms in different mammalian species is provided.
Keywords: pig; mitochondrion; mitochondrial biogenesis; splicing forms; expression